Prospects for pumped-hydro storage in Germany - Bjarne Steffen (University of Duisburg-Essen, Chair for Management Science and Energy Economics, 2011)
After a period of hibernation, the development of pumped-hydro storage plants in Germany regains momentum. Motivated by an ever increasing share of intermittent renewable generation, a variety of energy players considers new projects, which could increase the available capacity by up to 60% until the end of the decade. This paper analyzes the current development and evaluates the revenue potential as well as possible barriers. Overall, the prospects for new pumped-hydro storage plants have improved, even though profitability remains a major challenge.
Keywords: L94; Q42; Q48; 330; pumped-hydro energy storage; power plant investment; Germany